Case report: Clinical report of co-occurrence of pituitary adenoma and meningioma in the sellar region after meningioma treatment - Lu, Wang; Shengkai, Yang; Yu, Wang; Aimin, Li; Shiwei, Yan; Kang, Xie (Frontiers in Neurology, 2022)
The coexistence of meningioma and pituitary adenoma is very rare, especially in the same location after meningioma surgery. Here, we reported a case of coexisting meningioma and pituitary adenoma secondary to postoperative meningioma in the sellar region in a patient who had not received radiation therapy before the second surgery. A 61-year-old woman underwent craniotomy for tumor resection for sellar meningioma in 2017, and postoperative imaging showed no residual in the surgical area. In 2022, the patient had a history of decreased vision again. MRI showed the possibility of postoperative pituitary adenoma in the sellar region. The patient underwent endoscopic resection of the skull base lesion again. After surgery, the patient's visual symptoms improved. Histology of the sellar tumor showed both meningioma (meningeal epithelial type, WHO grade I) and pituitary adenoma in the same section. The coexistence of meningioma and pituitary adenoma is a very rare surgical entity. This report provides a theoretical basis for the selection of intracerebral tumor surgery and provides a diagnostic basis and treatment reference for patients diagnosed with meningioma and pituitary adenoma at the same time.